1995
DOI: 10.1002/jcp.1041620308
|View full text |Cite
|
Sign up to set email alerts
|

Receptor binding of PDGF‐AA and PDGF‐BB, and the modulation of PDGF receptors by TGF‐β, in human periodontal ligament cells

Abstract: The growth factors PDGF-AA and PDGF-BB have previously been shown to be potent mitogens for human periodontal ligament (hPDL) cells in vitro. Additionally, the mitogenic response to PDGF-AA has been shown to be specifically inhibited by TGF-beta. The purpose of the present investigation was to examine the binding of PDGF-AA and PDGF-BB, and the modulation of PDGF binding by TGF-beta, in hPDL cells. Scatchard analysis identified an average of 32,000 PDGF-AA high-affinity binding sites per cell with a dissociati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…Previous investigations have shown PDL cells to have predominantly PDGF-ot receptor subunits on the cell surface (Oates et al, 1995). It is our working hypothesis that there are endogenous factors within the periodontal wound that down-regulate the PDGF receptors in PDL cells, and ultimately limit the regenerative response to PDGF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations have shown PDL cells to have predominantly PDGF-ot receptor subunits on the cell surface (Oates et al, 1995). It is our working hypothesis that there are endogenous factors within the periodontal wound that down-regulate the PDGF receptors in PDL cells, and ultimately limit the regenerative response to PDGF.…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of the two receptor subunits has been shown to be a critical factor in the cellular response to a specific PDGF isoform (Heldin et al, 1988;Seifert et al, 1989). In addition, it has been shown that the expression of these receptors may be influenced by other growth factors and cytokines (Gilardetti et al, 1991;Oates et al, 1995). Therefore, an understanding of the modulating influences J Dent Res 77(10) 1998 of endogenous cytokines and growth factors present in a periodontal wound may be important in optimizing the regenerative potential of PDGF.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Platelet rich fibrin acts as a source of growth factors. Oates et al, have studied that growth factors (PDGF)-AA and PDGF-BB were major mitogens for human periodontal ligament cells, and transforming growth factor (TGF)-1 played a role as a regulator of the mitogenic responses [13]. Kawase et al, have proposed that platelet rich fibrin clot stimulates the formation of type 1 collagen in periodontal ligaments and osteoblastic cells invitro [12].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that the use of platelet rich fibrin helps is the better and faster healing of the operative site [11][12][13]. Platelet rich fibrin acts as a source of growth factors.…”
Section: Discussionmentioning
confidence: 99%